Case Report: Epithelioid angiosarcoma of the pleura - Dörr-Jerat, Niels Michael; May, Claus; Knolle, Jürgen; Schmidt, Sylke; Krüger, Marcus (Frontiers in Surgery, 2024)
We present the case of a patient with recurrent bilateral hemothorax. After misdiagnosis, a pleural manifestation of epithelioid angiosarcoma was diagnosed by further immunohistological staining. A 73-year-old woman presented with dyspnea for 3 days. She was in stable general condition, pain was denied, she had a history of cigarette smoking, she had no cardiopulmonary events, and she was not receiving any anticoagulation medication. Physical examination revealed decreased breath sounds on the left side, and her hemoglobin level was 7.0 mmol/l. Primary diagnoses, interventions, and outcomes.The initial chest X-ray showed a left-sided effusion. Hemothorax was then diagnosed. Further investigation revealed no evidence of malignancy (CT, EBUS, cytology, etc.). VATS was performed, and biopsies of pleural lesions did not reveal congruent findings for the hemothorax. Due to recurrent bilateral hemothorax with the need for erythrocyte transfusion, the patient underwent several operations, including histological sampling, without evidence of malignancy. After further processing, an additional pathological report revealed an epithelioid angiosarcoma defined by massively proliferating epithelioid cells strongly positive for ERG and CD31 and negative for CD34. The neoplastic cells coexpressed D2-40 (podoplanin). Finally, due to multiple cerebral metastases, palliative therapy was indicated.Physicians and pathologists treating spontaneous hemothorax need to have broad knowledge of the possible, sometimes rare, etiologies. If the clinical course and intraoperative findings do not agree with the histopathological results, this finding must be questioned, and further immunohistochemical staining is mandatory. Thus, in the case of recurrent hemothorax, angiosarcoma of the pleura should also be considered for differential diagnosis.